The impact of teacher engagement in an interactive webinar series on the effectiveness of financial literacy education. (9th September 2020) - Compen, Boukje; De Witte, Kristof; Schelfhout, Wouter
Abstract: This study examines whether online teacher professional development (OTPD), in the form of an interactive webinar series that encourages collaborative learning, improves student achievement. We conducted a randomised controlled trial with 1102 students, 45 teachers and 30 secondary schools in Flanders, Belgium. As a basis for the study, we developed a digital learning path aimed at improving student scores on financial literacy–a multidimensional key competence recently integrated into the curriculum. We demonstrate that the learning path improves student learning outcomes and that enhanced teacher involvement in this programme does not increase learning outcomes unless the teachers participate in the OTPD initiative. Teacher engagement in the webinar series generated student learning outcomes 0.39 standard deviations higher than those of students whose teachers did not receive this intervention, thus, confirming the effectiveness of the OTPD initiative. This effect was found immediately after programme implementation, and it persisted until at least 6 weeks later. As an underlying mechanism, we observe that engagement in the webinar series enhances teachers' self‐efficacy. Classroom observations suggest that engagement increases the frequency of providing students with content‐related help.